Have the Power-Rate Capabilities of Skeletal Muscles Received the Attention They Deserve? A Historical Perspective - James J. Perrine (International Journal of Sports Physical Therapy)
This commentary addresses a consequential, core, rate factor in muscle contractions. In 1960, an isokinetic-loading dynamometer was invented to assess that rate. A 1978 muscle force and power-velocity study using it, showed that the power-rate capability of a muscle group can be determined – when a sufficient loading velocity and force-development time are provided. Newton’s laws represent how existing forces can put yielding bodies in motion, thereby gaining mechanical energy, as well as how such forces first develop. Many of the ideas in this commentary are based on those laws of physics: a) all force developments in muscle contractions result from interactions of the mechanical energy – first converted from chemical energy within muscles’ tiny contractile cells – with loading bodies encountered both within and outside muscles; b) the rate at which that mechanical energy is first generated, in turn determines the rate at which requisite, timely forces develop against submaximal, functional loads and c) the composite contractile power-rate attained by muscle groups, under conventional free-weight loading, may be significantly restricted by an unrecognized, acceleration-triggered, neural mechanism. Two other isokinetic-loading training devices were invented, which were designed to help people regain an ability to ambulate and/or improve their physical fitness – in both cases via suitably elevated muscle power-rates. The purpose of this commentary is to draw attention to muscles’ functionally important, contractile power-rate capabilities, and to physical evidence of the ways they are apparently neurally restricted, so they can be reliably tested, and if found deficient, adequately improved, particularly by Sports PTs and ATCs. Level of Evidence: 5